Pokazateli gematologicheskogo gomeostaza v ocenke funkcional'nogo sostojanija sportsmenov - Gunina, L.; Rybina, I.; Kotlyarenko, L. (Science in Olympic Sport, 2020)
Objective. The formation of an algorithm for estimating hematologic homeostasis indices based on the analysis of data of modern literature and generalization of own results of cohort studies of elite athletes to control and manage the training process. Methods. Analysis and synthesis of data from scientific and methodological literature; laboratory and diagnostic, statistical. Results. Based on the analysis of literature data and the results of practical work of the authors, a complex of those parameters of erythrocyte hematological homeostasis, which can be used in the practice of sports training for mediated through changes in blood oxygen-transport function, assessment of aerobic endurance in representatives of different sports events, informa-tive control, and further training process management has been formed. Conclusion. The described complex of erythrocyte hematological homeostasis indices highlights almost all aspects of erythrocyte formation and their participation in the pro-cess of oxygen transfer, reflecting changes in aerobic work capacity, and can be used to assess the quality of life and current functional status of athletes.